The Epistle to the Hebrews in Modern Interpretation - Griffith, Sheila (2005)
This article focuses on the findings of modern scholars of the Epistle to the Hebrews on key historical-critical and thematic issues. We begin with an examination of the fundamental historical-critical questions of the authorship, date, audience, genre, and literary integrity of the Epistle to the Hebrews. Since these are notoriously thorny issues for the anonymous book of Hebrews, this survey asks the relevant questions, draws out the key insights and conclusions from top scholars, and emphasizes the points of scholarly consensus and disagreement. After probing the historical-critical questions, we then explore the scholarly debate over two of the main thematic issues of Hebrews: the overall aim of Hebrews and the striking and unique theme of priesthood so prominent in Hebrews. Again and again we encounter the overarching problem faced by most Hebrews scholars: there is just too little evidence—both internal and external—on which to base hypotheses about these foundational questions. While certain hypotheses can be securely dismissed-such as the early theory that Paul authored the book of Hebrews—for most questions the answers are not so clear-cut. The result is a plurality of proposals, most of which can be neither concretely verified nor resolutely dismissed from consideration.